2000
DOI: 10.1056/nejm200009143431103
|View full text |Cite
|
Sign up to set email alerts
|

Trial of a Supplemental Dose of Four Poliovirus Vaccines

Abstract: A supplemental dose of IPV has excellent immunogenicity and leads to increases in the titer of antibodies against type 3 poliovirus, whereas supplemental doses of the oral vaccines do not have these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 23 publications
6
31
0
11
Order By: Relevance
“…The study also demonstrated that higher humoral antibody titers are associated with decreased challenge virus excretion, as has been shown previously (4,19,27). bOPV increased antibody titers to poliovirus type 2, presumably because of boosting of cross-reacting neutralizing antibodies (31), since we did not isolate poliovirus type 2 from any stool samples.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The study also demonstrated that higher humoral antibody titers are associated with decreased challenge virus excretion, as has been shown previously (4,19,27). bOPV increased antibody titers to poliovirus type 2, presumably because of boosting of cross-reacting neutralizing antibodies (31), since we did not isolate poliovirus type 2 from any stool samples.…”
supporting
confidence: 87%
“…Although IPV administered after OPV effectively closes the humoral immunity gaps (2,18,19), its effect on intestinal mucosal immunity is lesswell characterized. Because mucosal immunity appears to wane rapidly (13), we initiated a trial in Northern India to assess whether IPV could boost mucosal immunity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lower antibody levels to poliovirus type 3 in comparison with types 1 and 2 have been reported previously in HIV-infected 28 and HIV-uninfected children. [28][29][30] In conclusion, this study underlines the optimization of selective strategies as the must for improving serological testing, in order to identify susceptible individuals. Therefore they are to be protected by supplementary strategies for booster doses, according to aligned schedules in terms of timing and number of vaccine doses.…”
Section: Discussionmentioning
confidence: 82%